The Malaysia-Indonesia Remittance Corridor : Making Formal Transfers the Best Option for Women and Undocumented Migrants - Hernández-Coss, Raúl (Washington, DC : World Bank, 2012)
The corridor between Malaysia and Indonesia is the second largest remittance outflow for Malaysia and the largest remittance inflow for Indonesia. In the East Asia and Pacific Region, Indonesia is the second largest supplier of labor migration with 680,000 overseas worker contracts concluded in 2006 alone. Since 2003, the number of contracts has more than doubled. Malaysia, in general, is a destination for foreign workers because of its economic performance and government recruitment policies aimed to alleviate labor shortages. In addition to these factors, the cultural and geographical proximity of Indonesia makes Malaysia a destination for both documented and undocumented Indonesian migrant workers. This report is a combined effort between the Financial and Private Sector Development and the East Asia and Pacific Social Development units of the World Bank. It is part of a series of studies under both the global Bilateral Remittance Corridor Analysis program and the Indonesia Female Migrant Worker Program. The report analyzes the transfer of remittances by Indonesian migrant workers known as Tenaga Kerja Indonesia (TKI). The main objective of this report is to contribute to policymaking efforts to increase the impact that remittances have on economic growth and poverty reduction in Indonesia, and investigate options for attracting more migrants to use the formal sector. The report aims to provide a descriptive overview of the Malaysia-Indonesia remittance corridor and to suggest some policy avenues for improving access to formal remittance transfer channels; increasing the transparency of the flows and cost structure; and facilitating the transfer of remittances, particularly for undocumented and female migrant workers.